Should Gamification be Personalized? A Self- deterministic Approach - Passalacqua, Mario; Sénécal, Sylvain; Frédette, Marc; Nacke, Lennart E.; Pellerin, Robert; Léger, Pierre-Majorique (Association for Information Systems transactions on human-computer interaction, 2021)
Information system (IS) gamification has been successful in many contexts. Yet, research has shown gamification’s success to vary between individuals. In this paper, we compare personalized versus non-personalized gamification in a warehouse management setting. We devised a 26-participant within-subject experiment in which we programmed goal setting and feedback gamification elements into a wearable warehouse management system to evaluate the effectiveness of personalized gamification in terms of user performance. We examined the extent to which personalized gamification succeeded by categorizing participants into one of six user types through the HEXAD scale and then evaluating their performance time and errors across user types and conditions. We found that personalized gamification is more effective than non-personalized gamification. We present and discuss the motivational mechanisms through which personalized gamification can be more effective.